Biology is not a hand-waving - Drobniak, Szymon (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2018)
Recenzja książki: J. Fodor, M. Piattelli-Palmarini, Błąd Darwina,  Wydawnictwo Naukowe PWN 2018
Keywords: evolutionary biology; philosophy